2014
DOI: 10.1055/s-0034-1382054
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity Interval Training Has Positive Effects on Performance In Ice Hockey Players

Abstract: In spite of the well-known benefits that have been shown, few studies have looked at the practical applications of high-intensity interval training (HIIT) on athletic performance. This study investigated the effects of a HIIT program compared to traditional continuous endurance exercise training. 24 hockey players were randomly assigned to either a continuous or high-intensity interval group during a 4-week training program. The interval group (IG) was involved in a periodized HIIT program. The continuous grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 35 publications
4
40
1
4
Order By: Relevance
“…Evidently after the process of data collection and processing, data processing results showed no significant increase in the dependent variable is 3, explosive power, speed, and agility. The results are consistent with previous studies such as Naimo et al [8], which called High-Intensity Interval Training Has Positive Effects on Performance In Ice Hockey Players reveal the same thing that the High-intensity Interval Training (HIIT) is able to provide a significant improvement to the output power in athletes. Astorino et al [9] revealed that HIIT workout can improve endurance and increase the speed of the athlete.…”
Section: Discussionsupporting
confidence: 92%
“…Evidently after the process of data collection and processing, data processing results showed no significant increase in the dependent variable is 3, explosive power, speed, and agility. The results are consistent with previous studies such as Naimo et al [8], which called High-Intensity Interval Training Has Positive Effects on Performance In Ice Hockey Players reveal the same thing that the High-intensity Interval Training (HIIT) is able to provide a significant improvement to the output power in athletes. Astorino et al [9] revealed that HIIT workout can improve endurance and increase the speed of the athlete.…”
Section: Discussionsupporting
confidence: 92%
“…It has recently been shown that postural control and risk of falls can improve after HIIT compared to the effects of a continuous exercise program in healthy and untrained young people [25], and also in patients with some type of pathology [6]. In the elderly, some randomized trials have studied the effects on cardiovascular and anthropometric outcomes after HIIT interventions [41,52].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have showed that HIIT can improve the aerobic performance in a short term beyond those found by endurance training with low intensity and high volume of exercise (Rodas et al, 2000; Laursen and Jenkins, 2002; Jensen et al, 2004; Helgerud et al, 2007; Laursen, 2010; de Araujo et al, 2015; Naimo et al, 2015). Due its high intensity feature, the HIIT may be excessive, and instead of improving, shows an unaltered performance responses, physiological stress, and overtraining symptoms (Billat et al, 1999).…”
Section: Introductionmentioning
confidence: 99%